MicroScale Thermophoresis (MST) for studying actin polymerization kinetics - Andrea Topf; Peter Franz; Georgios Tsiavaliaris (BioTechniques, 2017)
Here, we present a MicroScale Thermophoresis (MST)–based assay for in vitro assessment of actin polymerization. By monitoring the thermophoretic behavior of ATTO488-labeled actin in a temperature gradient over time, we could follow polymerization in real time and resolve its three characteristic phases: nucleation, elongation, and steady-state equilibration. Titration experiments allowed us to evaluate the effects of actin-binding proteins (ABPs) on polymerization, including DNase I-induced inhibition and mDia2FH1FH2 (mDia2)-assisted acceleration of nucleation. The corresponding rates of actin filament elongation were quantitatively determined, yielding values in good agreement with those obtained using the pyrene-actin polymerization assay. Finally, we measured the effect of myosin on actin polymerization, circumventing the problems of fluorescence quenching and signal disturbance that occur with other techniques. MST is a simple and valuable research tool for investigating actin kinetics covering a wide range of molecular interactions, with low protein consumption.